The association of sleep and late-night cell phone use among adolescents - Babak Amra; Ali Shahsavari; Ramin Shayan-Moghadam; Omid Mirheli; Bita Moradi-Khaniabadi; Mehdi Bazukar; Ashkan Yadollahi-Farsani; Roya Kelishadi (Elsevier, 2017)
Objective: This study aims to assess the relationship of late-night cell phone use with sleep duration and quality in a sample of Iranian adolescents. Methods: The study population consisted of 2400 adolescents, aged 12-18 years, living in Isfahan, Iran. Age, body mass index, sleep duration, cell phone use after 9 p.m., and physical activity were documented. For sleep assessment, the Pittsburgh Sleep Quality Index questionnaire was used. Results: The participation rate was 90.4% (n = 2257 adolescents). The mean (SD) age of participants was 15.44 (1.55) years; 1270 participants reported to use cell phone after 9 p.m. Overall, 56.1% of girls and 38.9% of boys reported poor quality sleep, respectively. Wake-up time was 8:17 a.m. (2.33), among late-night cell phone users and 8:03 a.m. (2.11) among non-users. Most (52%) late-night cell phone users had poor sleep quality. Sedentary participants had higher sleep latency than their peers. Adjusted binary and multinomial logistic regression models showed that late-night cell users were 1.39 times more likely to have a poor sleep quality than non-users (p-value < 0.001). Conclusion: Late-night cell phone use by adolescents was associated with poorer sleep quality. Participants who were physically active had better sleep quality and quantity. As part of healthy lifestyle recommendations, avoidance of late-night cell phone use should be encouraged in adolescents. Resumo: Objetivo: Este estudo visa avaliar a relação entre o uso de celular à noite e a duração e a qualidade do sono em uma amostra de adolescentes iranianos. Métodos: A população estudada consistiu em 2400 adolescentes, com idades entre 12 e 18 anos, residindo em Isfahan, Irã. Foram documentados a idade, índice de massa corporal, duração do sono, uso de celular após as 21h00 e prática de atividade física. Para avaliação do sono, utilizamos o questionário de Índice de Qualidade do Sono de Pittsburgh (PSQI). Resultados: A taxa de participação foi de 90,4% (n = 2257 adolescentes). A idade média (DP) dos participantes foi de 15,44 ± (1,55) anos; 1270 participantes relataram o uso do celular após as 21h00. Em geral, 56,1% das meninas e 38,9% dos meninos relataram sono de má qualidade, respectivamente. Os indivíduos que utilizaram celular à noite acordaram às 8h17 min (2,33) e os que não utilizaram acordaram às 8h03 min (2,11). A maior parte (52%) dos usuários de celular à noite apresentou má qualidade de sono. Aqueles sem nenhum tipo de atividade física apresentaram maior latência do sono que seus outros pares. Os modelos ajustados de regressão logística binária e multinomial mostraram que os usuários de celular à noite foram 1,39 vezes mais propensos a ter má qualidade do sono que seus outros pares (valor de p < 0,001). Conclusão: O uso de celular à noite por adolescentes foi associado a pior qualidade do sono. Os participantes fisicamente ativos apresentaram melhor qualidade e maior tempo de sono. Como parte das recomendações de estilo de vida saudável, os adolescentes devem ser incentivados a evitar o uso de celular à noite. Keywords: Sleep, Cell phone, Adolescents, Palavras-chave: Sono, Celular, Adolescentes